Incoherent scatter measurements of aurora-like ion beam distribution and ionospheric holes produced by the space shuttle flying over the radars at Jicamarca, Kwajalein, and Arecibo - Bernhardt, P.A. (2000)
In October 1997 and July 1999 during the STS-86 and STS-93 flights of the Space Shuttle, the crew performed experiments with controlled ion injections over the incoherent scatter radar (ISR) facilities located at Arecibo, Puerto Rico; Jicamarca, Perú; and Kwajalein, Marshall Islands. Ion beams were formed by charge exchange in the ionosphere of the high velocity neutral molecules exhausted by the Orbital Maneuver Subsystem (OMS) engines on the Space Shuttle. Pick-up ions were produced with energies between 2 and 10 eV depending on the orientation of the OMS engines relative to the vehicle orbit. The ions eventually recombined with electrons yielding electrón density depressions or holes.